2011
DOI: 10.1116/1.3644480
|View full text |Cite
|
Sign up to set email alerts
|

Effects of proton irradiation on dc characteristics of InAlN/GaN high electron mobility transistors

Abstract: Articles you may be interested inEffect of proton irradiation on thermal resistance and breakdown voltage of InAlN/GaN high electron mobility transistors J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…7 In this case, the devices exhibited little degradation when irradiated with 15, 40, and 105 MeV protons, while the greatest degradation was measured at the lowest proton energy due to the larger nonionizing energy loss of the 1.8 MeV protons. 7 The effects of proton dose on dc characteristics of InAlN/GaN HEMTs were reported by Lo et al, 8 which revealed that more degradation was induced at higher irradiation dose, with reductions of g m of 1% and 15%, and increase of channel resistance of 6% and 28% for HEMTs exposed to 2 Â 10 11 and 2 Â 10 15 cm À2 protons, respectively. In addition, it was also reported that there was little degradation at doses below 10 14 cm À2 in III-nitride HEMTs.…”
Section: Introductionmentioning
confidence: 88%
“…7 In this case, the devices exhibited little degradation when irradiated with 15, 40, and 105 MeV protons, while the greatest degradation was measured at the lowest proton energy due to the larger nonionizing energy loss of the 1.8 MeV protons. 7 The effects of proton dose on dc characteristics of InAlN/GaN HEMTs were reported by Lo et al, 8 which revealed that more degradation was induced at higher irradiation dose, with reductions of g m of 1% and 15%, and increase of channel resistance of 6% and 28% for HEMTs exposed to 2 Â 10 11 and 2 Â 10 15 cm À2 protons, respectively. In addition, it was also reported that there was little degradation at doses below 10 14 cm À2 in III-nitride HEMTs.…”
Section: Introductionmentioning
confidence: 88%
“…The proton energy at the exit of the cyclotron was 30 MeV. The proton energy at the sample was 5 MeV after passing through two aluminum degraders 15 . The thickness of each aluminum degrader was 2.7 mm.…”
Section: Methodsmentioning
confidence: 99%
“…5 The InAlN/GaN material system offers an attractive alternative to AlGaN/GaN for high power, high frequency applications. 15,16 The InAlN alloy can be synthesized lattice matched to GaN with large refractive index contrast and sheet charge density roughly twice that of typical AlGaN/GaN HEMTs. This sheet charge density is due to the more than 4Â increase in spontaneous polarization of In 0 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For both GaN and the most common heterostructure AlGaN/GaN used in nitride-based high electron mobility transistors (HEMTs), the effects of proton and electron irradiation are reasonably well documented. [10][11][12][13][14][15][16][17][18][19][20][21][22][23] The carrier removal rate in proton irradiated n-GaN was found to be in the range10 2 -10 3 cm À1 depending on the proton energy and was shown to increase for higher donor concentrations. 22 The most prominent defect levels created are deep traps with activation energies of 0.13, 0.16-0.18, 0.2-0.21 eV, while electron irradiation created the 0.16-0.18 eV traps due to N vacancies.…”
Section: Introductionmentioning
confidence: 95%